When change matters: the effect of dependent interviewing on survey interaction in the British Household Panel Study - S.C. Noah Uhrig; Emanuela Sala (University of Essex, Institute for Social and Economic Research (ISER), 2009)
We examine how dependent interviewing affects verbal interaction between interviewers and respondents in questions obtaining current employment details in the British Household Panel Study. Respondents experience few cognition problems when answering DI questions, but interruption and elaboration are likely at PDI questions. These behaviours occur when respondent circumstances have changed. Departures from standardised interviewing are also likely when circumstances change. DI seems to reduce the accuracy of detail about such change since we observe interviewer behaviour that others find to produce inaccurate data. Nevertheless, these results may explain why DI reduces the odds of spurious change between waves of panels.
Keywords: 330